PERANAN KESULITAN EKONOMI, KEPUASAN KERJA DAN RELIGIUSITAS TERHADAP KESEJAHTERAAN PSIKOLOGIS - M Noor Rochman Hadjam; Arif Nasiruddin (Jurnal Psikologi, 2003)
This study examined the effects of economic pressure, job satisfaction and religiosity on psychological well being (PWB). 53 subjects (40 male, 13 female) rated themselves with 4 self rating scales. All subjects were married, and aged between 25-29 year (M=39.3 years). Regression analysis was used in this study. Results revealed that there is significant effect of three factors (economic pressure, job satisfaction, and religiosity) on PWB (Freg=3,987 p